Service oriented architecture-based design of bank-ATM and its verification with Petri-net. (3rd November 2021) - Nath, Amar; Rath, Santanu Kumar
In the present era, IT-enabled business applications are very much observed to be pervasive and felt to be essential to manage an organisation. An organisation needs to update and upgrade its strategies to meet the challenges by adopting an IT-enabled solution to meet the agile customer requirements and market demand. Service-oriented architecture (SOA) is one of the various architectural styles that provides agility to the organisation. SOA can help to meet different changes in requirements, viz., service composition, model-driven development, and service virtualisation. This paper illustrates the application of SOA in designing and implementing automated teller machine (ATM) services, helpful in banking transactions. The incorporation of various services and their orchestration is implemented by using business process execution language (BPEL). It is very much essential to develop a proper BPEL process and validate it. In this study, the validation of the BPEL model is carried out by using the Petri-net tool.